INDONESIAN EFL LEARNERS’ BELIEFS ABOUT ADVANTAGES OF SONGS IN LANGUAGE LEARNING - Suswati Hendriani; Mukhaiyar Mukhaiyar; Martin Kustati; Hendra Eka Putra; Jepri Ali Saiful (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Abstract: Despite a considerable body of studies, little attention is given to the advantages of using songs in learning (learner-centred). The study, therefore, is aimed at eliciting Indonesian EFL learners’ beliefs about the advantages of using songs for their language learning. Researching the research phenomenon through a qualitative study using a case study design, in-depth interview technique was applied to collect the data of the learners’ beliefs from eleven university learners majoring English. This study indicated an interesting finding that it was perceived that the learners believed that there were some advantages of using songs in learning English: increasing their EFL learning in the aspects of language skills (listening and speaking), language components (vocabulary mastery and pronunciation), their knowledge, their confidence and relaxation, and improving their mood and focus. Thus, it is recommended that songs be used either in teachers’ EFL teaching and in learners’ EFL learning. Abstrak: Meskipun telah banyak penelitian yang dilakukan, namun masih sedikit perhatian yang diberikan tentang manfaat penggunaan lagu dalam pembelajaran (berpusat pada peserta didik). Oleh karena itu, penelitian ini bertujuan untuk mengungkap keyakinan pembelajar Bahasa Inggris sebagai bahasa asing di Indonesia tentang manfaat penggunaan lagu dalam pembelajaran bahasa asing mereka. Meneliti fenomena melalui studi kasus, teknik wawancara mendalam diterapkan untuk mengumpulkan data tentang keyakinan sebelas mahasiswa jurusan Bahasa Inggris. Penelitian ii menunjukkan temuan yang menarik bahwa peserta didik percaya bahwa ada beberapa keuntungan dari pemanfaatan lagu dalam pembelajaran bahasa Ingris mereka pada aspek keterampilan bahasa (menyimak dan berbicara), komponen bahasa (penguasaan kosa kata dan pengucapan), pengetahuan mereka, kepercayaan diri dan relaksasi mereka, serta memperbaiki suasana hati dan fokus mereka. Oleh karena itu, disarankan agar lagu digunakan dalam pengajaran bahasa Inggris oleh guru maupun dalam pembelajaran bahasa Inggris oleh peserta didik.